Macroscopic brain gray matter staining: historical protocol overview and neuroanatomy learning applications in second-year medical students - Villegas-Gomez, Gustavo Adolfo; Figueredo, Luisa F.; Ramirez, A. D.; Quiroga-Padilla, Pedro Jose; Rueda-Esteban, Roberto (Frontiers in Neuroanatomy, 2023)
Macroscopic staining in anatomical samples of the central nervous system is a technique that has been used for decades to achieve better differentiation of multiple gray matter structures, such as the cortex, basal ganglia, and cerebellar nuclei, amongst others. Staining methods are based on using the different components of the brain, mainly the lipids present in the white matter. These techniques have been progressively forgotten while computer renderings are increasing; however, as a primary exposure to surgical anatomy, stained brain specimens are considered a helpful tool. We aim to summarize different staining techniques, their principles, and their current applications for neuroanatomy learning purposes. Four grey matter staining protocol descriptions (Mulligan's, Robert's, Alston's, and Prussian Blue) and second-year medical students' Likert scale surveys focused on their perception using the stained sections were performed. Results showed that the different techniques of macroscopic stains for brain tissue are based on the lipids and reactant interactions, intending to increase the white matter (WM) and gray matter (GM) contrast. The search also showed that most staining protocols would take two days to develop. Efficient preservation options include submerging the sections in formaldehyde solutions, formaldehyde-free solutions, ethanol, or applying plastination techniques. Based on the student's perspective, the stained slices seem to be a valuable alternative to facilitate the study and identification of the basal ganglia and their relationships with the white matter (from 51.2% to 72% based on the Likert scale) compared to the not stained sections. In conclusion, macroscopic staining in brain tissue continues to be a valuable tool for comprehensively studying the brain. Further research on the stained specimens' utility as teaching tools is needed.